ISLAMIC DIDACTIC LITERATURE IN THE NOVEL “CINTA DI UJUNG SAJADAH” BY ASMA NADIA - Erlinda Nofasari; Dadang Sunendar; Sumiyadi Sumiyadi; Vismaia Sobariah Damaianti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research aimed to describe didactic literature in the Islamic novel Cinta Di Ujung Sajadah (CDUS, 2012) by Asma Nadia in terms of the contents/expressions of Islamic literary didacticism. This type of research was qualitative research using descriptive methods. Data analysis was carried out based on the didacticism expression theory. The results showed that the Islamic novel CDUS (2012) by Asma Nadia (1) has contents/expressions that are in accordance with the aqeedah, sharia, ihsan (morals). (2) is a didactic literature that provides moral, religious, and social teaching. (3) charged dimensions of factual, conceptual, procedural, and metacognitive knowledge. (4) can be used as sources and solutions based on sharia science. Islamic didactic literature found in the novel CDUS (2012) by Asma Nadia is very relevant to be used as a source of literacy to improve the morale of students.